Quais tipos, formas e funções das células nos seres vivos? - Daniel, Sandro Natal; Penso, Jucinei; Carraro, Marcia Regina Simpioni (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2023)
>>> ver pdf